Prevalence and influencing factors of non-suicidal self-injury among secondary school students seeking medical treatment - Fu, Xiaonv; Zhao, Mingzhe; Luo, Mingjin; Ye, Chenxia; Wei, Yating; Cao, Janyue; Song, Haidong (Frontiers in Psychology, 2025)
BackgroundNon-suicidal self-injury (NSSI) is a significant risk factor for suicide and has emerged as a growing public health concern among adolescents. Despite its severity, the consultation rate for NSSI among secondary school students remains notably low. While previous research has explored formal and informal help-seeking behaviors related to NSSI. In order to address this gap, this study aims to investigate the consultation rate and identify key factors associated with seeking medical treatment for NSSI.MethodsWe conducted a cross-sectional study involving participants aged 12–20 years. The types and frequencies of NSSI were assessed using the Adolescent Self-Harm Questionnaire. Treatment-seeking behavior was evaluated through a self-developed questionnaire. Participants were recruited from both non-clinical settings (schools) and clinical settings (a tertiary hospital). Logistic regression analyses were employed to identify factors associated with seeking professional consultation for NSSI.ResultsThe consultation rate for NSSI was 15.64%. A total of 1,777 valid questionnaires were collected, including 1,586 non-clinical samples from secondary schools and 191 clinical samples. Factors positively associated with seeking medical treatment among secondary school students with NSSI included family awareness (OR = 10.452, 95%CI = 5.719–19.100, p < 0.001), being an only child (OR = 4.452, 95%CI = 1.847–10.730, p = 0.001), help-seeking behavior (OR = 2.694, 95%CI = 1.285–5.647, p = 0.009), older age (OR = 2.137, 95%CI = 1.630–2.801, p < 0.001), female (OR = 1.919, 95%CI = 1.002–3.676, p = 0.049), family income (OR = 1.699, 95%CI = 1.214–2.377, p = 0.002). No statistically significant associations were observed for educational stage, residential area, maternal education level, or maternal relationship in relation to treatment-seeking behavior.ConclusionThis study reveals a low consultation rate (15.64%) for NSSI among adolescents. Family awareness, being an only child, seeking help or not, age, and family income are factors influencing the seeking of medical treatment. Among these, family awareness has the greatest impact, followed by Seeking help or not. We appeal to parents to pay attention to the mental health of adolescents, build a good family relationship, and make efforts to promote the seeking of medical treatment.